2007
DOI: 10.1007/s10792-007-9116-z
|View full text |Cite
|
Sign up to set email alerts
|

Refractive effect of the horizontal rectus muscle recession

Abstract: In spite of being statistically significant in some parts, the amounts of refractive and corneal topographic changes were not clinically remarkable. Therefore, it does not seem necessary to perform cycloplegic refraction early after horizontal rectus muscle recession; however, a precise refraction in all cases of strabismus should not be deferred later than 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 7 publications
8
31
0
3
Order By: Relevance
“…Hong and Kang [5] also reported that small statistical astigmatic changes did not seem to be clinically important. In our study, cylinder power and axis of induced astigmatism showed statistically significant differences compared with the preoperative values, but these astigmatic changes did not affect vision changes in either group, in agreement with the previous studies [527]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hong and Kang [5] also reported that small statistical astigmatic changes did not seem to be clinically important. In our study, cylinder power and axis of induced astigmatism showed statistically significant differences compared with the preoperative values, but these astigmatic changes did not affect vision changes in either group, in agreement with the previous studies [527]. …”
Section: Discussionsupporting
confidence: 93%
“…No statistically significant difference was found between preoperative and postoperative BCVA (logMAR) either in group 1 or group 2 (all p > 0.05 in both groups), and there was also no inter-group difference (all p > 0.05). Rajavi et al [27] reported that LR recession induced significant change only in the astigmatic axis toward with-the-rule astigmatism, and not in astigmatic power or SE at 1 month or 3 months after surgery. Although the authors did not directly evaluate preoperative or postoperative visual acuity, they reported that shift of axis would not be practically notable, considering insignificant alteration in astigmatic power.…”
Section: Discussionmentioning
confidence: 99%
“…When Seo and colleagues [23] analyzed corneal topography, they found a significant increase in higher order aberrations (including quatrefoil, pentafoil, secondary coma, secondary trefoil, and secondary astigmatism) at postoperative week 1, which resolved within 1 month postoperatively. The significant increase in WTR astigmatism Bagheri et al [12] found after 4-muscle recession persisted when evaluated 6-8 weeks postoperatively. The myopic shift and astigmatic changes earlier…”
Section: Transience Versus Permanencementioning
confidence: 82%
“…Noh et al [17] found a significant increase in WTR astigmatism associated with BLR recession (0.30 AE 0.46, P ¼ 0.005.). When looking at 4-muscle recession in patients with nystagmus, Bagheri et al [12] found a significant increase in WTR astigmatism (þ0.70 AE 0.80 D, P < 0.0002). Hong and Kang [13] used power vector analysis, a method which accounts for both physical and optical properties affecting refraction, to show that WTR astigmatism increased for 3 months postoperatively and was sustained for 6 months of postoperative follow-up.…”
Section: Change In Astigmatismmentioning
confidence: 99%
“…Furthermore, the effect of strabismus surgery on astigmatism is also debatable. Some reported that recession of a single rectus muscle was associated with an increase in power in the meridian of the recessed muscle [2], whereas others reported a decrease in the power of this meridian [5-7,10,11]. Part of these discrepancies may be caused by methodological difficulties in representing refractive power changes.…”
mentioning
confidence: 99%